Introducing an abdominal paracentesis procedure box in the acute gastroenterology ward environment: a quality improvement and audit project - Sean Gill; Margaret Corrigan; Ashley Coope; Fred Fyles (Clinical Medicine)
Introduction: The development of ascites is a significant milestone in the disease trajectory of patients with chronic liver disease.1 Safe and timely abdominal paracentesis has been shown to reduce in-patient mortality and improve patients' symptoms.2 However, in our institution, we identified delays in performing therapeutic paracentesis, leading to postponed investigations, prolonged symptom burden and increased length of hospital stay.To address these challenges, we designed a quality improvement project aimed at enhancing the efficiency of the in-patient abdominal paracentesis service. Our objectives included optimising procedural workflow, evaluating the utilisation of Local Safety Standards for Invasive Procedures (LocSSIP) documentation and identifying education and training needs among medical and nursing staff. Materials and Methods: We conducted a retrospective analysis of electronic patient records to evaluate trends in large-volume paracentesis (LVP) performed during acute admissions in January 2024. Following this, we surveyed resident doctors in the gastroenterology department to identify barriers to timely paracentesis.Based on the insights gathered, we introduced an abdominal paracentesis procedure box designed to streamline the process. To assess its impact, we conducted pre- and post-intervention time and motion studies, measuring the time required to collect the necessary equipment before performing paracentesis. Results and Discussion: Our analysis identified 14 patients who underwent LVP during an acute admission in January 2024. Notably, 70% of these procedures were performed in the afternoon, contributing to delays in discharge in two cases. Additionally, compliance with LocSSIP documentation was inconsistent, with pre-insertion LocSSIPs completed in 73% of cases, while post-insertion LocSSIPs were only completed in 27%.The survey of resident doctors revealed multiple barriers to timely paracentesis, including difficulties in locating equipment, unfamiliarity with procedural steps and incomplete documentation. Before the intervention, the average time required to gather the necessary consumable equipment was 14 min, 57 s.To address these issues, we introduced a standardised ascitic drain procedure box (Fig 1), containing all required equipment, along with a corresponding checklist. This was implemented on both acute gastroenterology wards to facilitate easier access. Additionally, we incorporated paracentesis training into resident doctors' induction programmes and introduced a monthly simulated practical teaching session using a clinical skills mannequin to improve procedural confidence.Post-intervention analysis demonstrated a significant improvement, with the average time taken to collect equipment reduced to just 2 min, 9 s. Feedback from medical staff was overwhelmingly positive, highlighting the benefits of a logical layout and a standardised process. Notably, 100% of respondents reported increased confidence in locating equipment, and procedures were performed earlier in the day, improving overall efficiency. Conclusion: The successful implementation of an abdominal paracentesis procedure box significantly reduced equipment collection time, enhanced procedural efficiency, and improved resident doctor satisfaction and confidence in performing abdominal paracentesis and their overall training experience.This has facilitated awareness of clinical governance safety protocols and reduces variability in practice and seeks to minimise procedural risks. We recommend the adoption of procedure boxes or similar variations in other departments seeking to standardise practice within an institution.